1988
DOI: 10.1084/jem.167.2.676
|View full text |Cite
|
Sign up to set email alerts
|

T cell receptor gamma/delta chain diversity.

Abstract: The TCR-gamma and -delta chains of six murine hybridomas were compared by one-dimensional SDS-PAGE and two-dimensional NEPHGE/SDS-PAGE analysis. This allowed the identification of three distinct gamma chains (gamma a, gamma b, and gamma c) and three distinct delta chains (delta a, delta b, and delta c). Four gamma/delta chain combinations (gamma a delta a, gamma b delta b, gamma b delta c, and gamma c delta a) were observed. These results indicate that multiple forms of the delta chain are expressed and sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1988
1988
1991
1991

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…In situ immuno fl uorescent staining of skin with CD3, Vy3, and Thy-l antibodies also indicates that most if not all dEC express Vy3 (E. Payer, personal com munication). While there have been reports of skin-derived hybridomas that express other TCR, including both rx{3 and yb (19,(46)(47)(48), the pre ponderance of evidence indicates that the skin is virtually exclusively populated by Vy3+ T cells. While these results suggested that the dEC TCR repertoire might be severely restricted in combinatorial diversity, there remained the possibility of diversity contributed by junctional events.…”
Section: Skin Epithelium (Dec S-iel)mentioning
confidence: 99%
“…In situ immuno fl uorescent staining of skin with CD3, Vy3, and Thy-l antibodies also indicates that most if not all dEC express Vy3 (E. Payer, personal com munication). While there have been reports of skin-derived hybridomas that express other TCR, including both rx{3 and yb (19,(46)(47)(48), the pre ponderance of evidence indicates that the skin is virtually exclusively populated by Vy3+ T cells. While these results suggested that the dEC TCR repertoire might be severely restricted in combinatorial diversity, there remained the possibility of diversity contributed by junctional events.…”
Section: Skin Epithelium (Dec S-iel)mentioning
confidence: 99%
“…T cell hybrids used in this study were DN2 .9, DN7 .1.13, DN7 .3, DN12.1 (26), generously provided by Ada Kruisbeek (National Institutes ofHealth, Bethesda, MD) ; FT45.1 and PDN3.1 (27) were provided byJeff Bluestone (University of Chicago, Chicago, IL); and 33BTE .67 .1 was provided by Willi Born (National Jewish Hospital, Denver, CO).…”
Section: Methodsmentioning
confidence: 99%
“…(Fig 2, right) Two-dimensional nonreduced-reduced SDS-gel analysis of TCR expression in antigen-specific T cell clones . Immunoprecipitation of surface-labeled cell lysates with the anti-Cpl (left) and anti-Cp2 (right) antisera were performed as described (9,10), and then run nonreduced in the first (horizontal) dimension and reduced in the second (vertical) dimension. Precoated the anti-Cp2 immunoprecipitate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Journal of Experimental Medicine " Volume 168 December 1988 2379-2384 2379 1251 by the lactoperoxidase method, and immunoprecipitations and gel electrophoreses were performed as described previously (9,10) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation